BEYOND IAS 38 [A look to the future of Intangible Assets] - Valdivia Ramos, Román Arturo (2012)
Intangible assets are assets that generate and create value things. The product itself does not create value; the value is what gives the brand, reputation, corporate culture. Therefore, it is difficult that the current accounting can record these intangible assets, as it was not created and designed for it. Accounting is made to record tangible or material things, giving an economic value to such things. Would you sell your company for the amount that reflects the accounting? Surely the answer is NO, because there is any number of intangibles that will raise the sales price, that is what we call extra-value accounting. However, the accounting records some intangible assets, and these are a few: 1. Concessions 2. Science and Other Rights 3. Patents 4. Industrial Property (Brands) 5. Computer Programs (Software) 6. Development and operational costs 7. Formulas, designs and prototypes 8. Reservations of Extractable Resource 9. Goodwill 10. Other Intangible Assets And we finished counting. Then, the current Accounting through the NIC-38 Intangible Assets, only can measure and account these intangibles except the numeral 10. But ... what are the other Intangible Assets?